KWT KENCONO WUNGU TRAINING IN AN EFFORT OPTIMIZING DIGIT-BASED MARKETING THROUGH FACEBOOK WITH STUDENT TEACHING - Prambada Kirsaputa, Imam; Iga Pramesty, Nadia; Afivaturokhmah, Neila; Raharjo, Anisyah; Rinofah, Risal; Fauzi, Fitriya (SMARTINDO, 2024)
This socialization program aims to provide understanding and skills regarding digital marketing through the Facebook platform to KWT Kencono Wungu members who manage layinghens businesses. The activity was held on October 20, 2024 located in Blambangan village, Jogotirto, Berbah, Sleman, Yogyakarta, attended by 14 members out of a total of 20 invitations. The materials presented included the basics of digital marketing, strategies for using Facebook for promotion, and the application of the Tamansiswa teaching principles of Niteni, Nirokke, Nambahi in entrepreneurship. During the socialization, participants showed high enthusiasm and actively discussed, especially regarding the application of effective marketing strategies. The evaluation results showed that the majority of participants felt that they got significant benefits from this training and hoped for similar activities in the future. With this socialization, it is expected that KWT members can be more optimal in marketing their egg products, increasing competitiveness, and supporting local economic growth.